INTEGRASI FILSAFAT PADA PEMBELAJARAN BAHASA ARAB DALAM MENCIPTAKAN PEMBELAJARAN BAHASA YANG HOLISTIK DAN KRITIS - Kodri, Jalilatul; Bakar, M. Yunus Abu (LP2M IAIN Sultan Amai Gorontalo, 2026)
This research aims to examine the integration of philosophy of science in Arabic language learning in order to transform it into a holistic, critical, and contextual approach, so as to go beyond the achievement of linguistic competence alone. This research uses a library research method with content analysis techniques on relevant primary and secondary sources, such as books, journals, and scientific articles. The synthesis of ontological, epistemological, and axiological approaches results in a learning transformation with three main characteristics. First, holistic, which integrates the cognitive (analysis of language structure), affective-spiritual (internalization of values), and psychomotor (active use of language) domains simultaneously. Second, critical, by emphasizing in-depth analysis, evaluation, and criticism of the text through the lens of epistemology. Third, contextual, which is to relate language to socio-cultural realities and encourage religious moderation through discussions of diverse interpretations of texts. The integration of philosophy of science transforms the paradigm of Arabic language learning to be more substantive and empowering, which not only builds language proficiency but also shapes students' character and critical thinking skills to answer future challenges.